(untitled) (Revista de Estudos da Linguagem, 2024)
This survey is an attempt to reconsider the origin of the Classical Arabic invariable proclitic particles sawfa and sa- marking the future tense with the imperfect form yaf‘alu. Classical Arabic is the only Semitic language using two particles to indicate the future, with the exception of the Modern Arabic dialects and the Modern Neo-Aramaic varieties. Due to the historical linguistic contacts with other Semitic languages like Aramaic, Classical Arabic developed a new particle to express the future tense, as a linguistic innovation. The paper demonstrates that sa- is not a reduced form of sawfa, but a native Arabic abbreviated form to stress the future; by contrast, sawfa is a loan that entered Arabic and was juxtaposed with sa- as a borrowed particle.